A Simple Image Analysis Method for Determination of Glucose by using Glucose Oxidase CdTe/TGA Quantum Dots - Javad Tashkhourian; Morteza Akhond; S. Hooshmand; T. Khosousi; B. Hemmateenejad (Analytical and Bioanalytical Chemistry Research, 2014)
Glucose, as the major energy source in cellular metabolism, plays an important role in the natural growth of cells. Herein, a simple, rapid and low-cost method for the glucose determination by utilizing glucose oxidase and CdTe/thioglycolic acid (TGA) quantum dots (QDs) on a thin layer chromatography (TLC) plate has been described. The detection was based on the combination of the glucose enzymatic reaction and the quenching effect of H2O2 on the CdTe/TGA quantum dots photoluminescence. This QDs-based assay exhibits several advantages. Enzyme immobilization and QDs modification process are not required and the high stability of the QDs towards photobleaching is beneficial to this sensing system. The proposed method is linear in concentration range of 1.00 × 10-1-3.00 × 10-5 M of glucose and has a detection limit of 1.25 × 10-8 M. The results of real sample analysis show that the glucose oxidase CdTe/TGA QDs system would be a promising glucose-biosensing system.